1977
DOI: 10.1063/1.435223
|View full text |Cite
|
Sign up to set email alerts
|

The Raman spectrum of NaCN under hydrostatic pressure

Abstract: We have measured the Raman spectrum of NaCN in the two orthorhombic low temperature phases under hydrostatic pressure up to 6 kbar. At the order–disorder phase transition from the disordered phase D252h to the ordered phase D132h the unit cell doubles and new phonon bands fold from the zone boundary to the center and appear in the Raman spectrum. We analyze the transition group theoretically and assign the different phonon bands in the Raman spectrum. The pressure shift of the CN− librational mode is larger th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1978
1978
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Since no other spectroscopic changes accompany this phenomenon it is probable that it merely indicates that the pressure dependence of v(CN) is non-linear, rather than a structural change. We note that the initial slope of the v(CN) plot is close to that found for CN-doped NaCl, 0.54 cm-' kbar-1,25 at 90 K. However, Dultz et al 23 have very recently reported dco/dP of 0.9 cm-l kbar-I for NaCN (11) in the range up to 6 kbar : the reason for the discrepancy is not clear.…”
Section: ( Wsupporting
confidence: 63%
“…Since no other spectroscopic changes accompany this phenomenon it is probable that it merely indicates that the pressure dependence of v(CN) is non-linear, rather than a structural change. We note that the initial slope of the v(CN) plot is close to that found for CN-doped NaCl, 0.54 cm-' kbar-1,25 at 90 K. However, Dultz et al 23 have very recently reported dco/dP of 0.9 cm-l kbar-I for NaCN (11) in the range up to 6 kbar : the reason for the discrepancy is not clear.…”
Section: ( Wsupporting
confidence: 63%
“…These values, which were obtained by Brillouin scattering experiments in a range of hydrostatic pressure up to several kbar, agree fairly well with our results. Raman spectra of NaCN and KCN under hydrostatic pressure have been studied by Dultz, Krause & Winchester (1977) and Dultz & Krause (1978). These authors derived Grtineisen parameters for the transverse-acoustical soft mode connected with c44, without giving further details of nonlinear elastic properties.…”
Section: Discussionmentioning
confidence: 99%
“…Raman spectroscopy is often useful to infer longer unit cell (Brillouin zone folding) of phase involved in a crystallographic phase transition. If a vibrational branch (such as a longitudinal optical vibration) is subject to n folds of its Brillouin zone, it will give rise to n-1 new evenly spaced vibrations of comparable intensity [7,29]. Suppose the unit cell approximately doubles along c axis at low temperature T. This will permit Raman spectra of one extra very low frequency optical phonon, which would be described as the Brillouin zone boundary in the high-T phase.…”
Section: Raman Spectroscopymentioning
confidence: 99%